Digital Literacy Skills for Family History Research - Wilkinson, Jaci; Bond, Natalie (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – In this case study, an archivist and librarian teamed up to teach an introductory course on family history research for adult learners at their university’s lifelong learning centre. In response to students’ relative lack of digital skills, the instructors developed a new set of introductory skills that they believe are essential for genealogy research.Methods – Authors conducted pre- and post-course surveys to determine student expectations and the extent to which the course met those expectations. Authors coded one of these surveys.Results – Course assessment and class activities exposed the need for a set of digital skills that go beyond a literacy framework to assist family history researchers. After analyzing key themes found in pre- and post-course assessment, authors developed a new tool for genealogy instructors titled Introductory Digital Skills and Practices in Genealogy (IDSG).Conclusion – Archivist/librarian collaborations are an excellent way to cultivate needs-based teaching and outreach opportunities in our wider communities, particularly for adult learners. The Introductory Digital Skills and Practices in Genealogy tool is meant to inspire and assist other library professionals who want to teach family history research, serving as a reminder to centre teaching tangible digital skills as a focal point of instruction.